Is Upregulation of Sarcolipin Beneficial or Detrimental to Muscle Function? - Bal, Naresh C.; Gupta, Subash C.; Pant, Meghna; Sopariwala, Danesh H.; Gonzalez-Escobedo, Geoffrey; Turner, Joanne; Gunn, John S.; Pierson, Christopher R.; Harper, Scott Q.; Rafael-Fortney, Jill A.; Periasamy, Muthu (Frontiers in Physiology, 2021)
Sarcolipin (SLN) is a regulator of sarco/endo plasmic reticulum Ca2+-ATPase (SERCA) pump and has been shown to be involved in muscle nonshivering thermogenesis (NST) and energy metabolism. Interestingly, SLN expression is significantly upregulated both during muscle development and in several disease states. However, the significance of altered SLN expression in muscle patho-physiology is not completely understood. We have previously shown that transgenic over-expression of SLN in skeletal muscle is not detrimental, and can promote oxidative metabolism and exercise capacity. In contrast, some studies have suggested that SLN upregulation in disease states is deleterious for muscle function and ablation of SLN can be beneficial. In this perspective article, we critically examine both published and some new data to determine the relevance of SLN expression to disease pathology. The new data presented in this paper show that SLN levels are induced in muscle during systemic bacterial (Salmonella) infection or lipopolysaccharides (LPS) treatment. We also present data showing that SLN expression is significantly upregulated in different types of muscular dystrophies including myotubular myopathy. These data taken together reveal that upregulation of SLN expression in muscle disease is progressive and increases with severity. Therefore, we suggest that increased SLN expression should not be viewed as the cause of the disease; rather, it is a compensatory response to meet the higher energy demand of the muscle. We interpret that higher SLN/SERCA ratio positively modulate cytosolic Ca2+ signaling pathways to promote mitochondrial biogenesis and oxidative metabolism to meet higher energy demand in muscle.